2019
DOI: 10.1371/journal.pone.0225726
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional SCCmec types and low prevalence of the Panton-Valentine Leukocidin exotoxin in South African blood culture Staphylococcus aureus surveillance isolates, 2013-2016

Abstract: Staphylococcus aureus is a healthcare-associated pathogen that can harbour multiple antimicrobial resistance determinants and express multiple virulence factors e.g. Panton-Valentine Leukocidin (PVL). Unknown staphylococcal cassette chromosome mec (SCCmec) typing patterns were previously observed among 11% (n = 52) of methicillin-resistant S. aureus (MRSA) isolates; we further investigated these as well as the proportion of PVL, encoded by lukS/F-PV, in 761 S. aureus isolates from patients with a diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 27 publications
5
14
1
Order By: Relevance
“…We observed that, in addition to β-lactam resistance, the isolates classified as t064/t1257/t6238-CC8 harbouring the SCC mec IV element also possessed genes ( aacA-aphD , dfrA , and ermC ) mediating resistance to aminoglycosides, trimethoprim and macrolides, respectively. The presence of these resistance determinants in our archived isolates support existing data [20,21] that this multi-resistant lineage is established and well adapted in the hospital environment in South Africa.…”
Section: Discussionsupporting
confidence: 88%
“…We observed that, in addition to β-lactam resistance, the isolates classified as t064/t1257/t6238-CC8 harbouring the SCC mec IV element also possessed genes ( aacA-aphD , dfrA , and ermC ) mediating resistance to aminoglycosides, trimethoprim and macrolides, respectively. The presence of these resistance determinants in our archived isolates support existing data [20,21] that this multi-resistant lineage is established and well adapted in the hospital environment in South Africa.…”
Section: Discussionsupporting
confidence: 88%
“…A number of unknown types was noted from 2010 to 2017. We subsequently further investigated a proportion ( n = 52) of the unknown types from 2013 to 2016 and found that the majority of the isolates were interpreted as type I-like, type II-like and type III-like [ 30 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Singh-Moodley et al have characterized MRSA isolates from blood cultures from 2013 to 2016 in South Africa, and reported pvl positivity rate to be 25% [39]. PVL-MRSA has been also linked to nosocomial infections in which hospital transmission of CA-MRSA had occurred in the US [40], highlighting the important source of CA-MRSA as a public health threat in hospitals.…”
Section: Discussionmentioning
confidence: 99%